The Christology of Bonaventure - Lance H. Gracy (Religions)
Scholarly discussion on Bonaventure’s Christology has tended to favor its Trinitarian, historical, and epistemological dimensions. Of note is Bonaventure’s notion of Christ as medium metaphysicum: the very depth and center of history according to knowing, learning, and mystical desire. What is perhaps less considered with respect to these topics, but nevertheless evident in contemporary scholarship, is the extent to which Bonaventure’s Christological structure informs an essential relation between creation and glorification. This essay explores these topics with attention to contemporary Bonaventure scholarship to offer insights on the ongoing importance of Bonaventure’s Christology for posterity, especially as it relates to a Bonaventurian theology of creation.